Analysis of the Quality of Pilgrimage Walkways in Historical Context Around Holy Places Case Study: Bagh Hassan Khan Passage in the Peripheral Context of Imam Reza Holy Shrine - Naser Kazemzadeh Gharghabi, Amidoleslam Saghatoleslami (Mathematical Statistician and Engineering Applications, 2023)
Pilgrimage walkways are one of the obvious linear elements of most pilgrimage cities in the world that in such urban spaces, pilgrims and tourists faces from their entrance to that city to the time of arriving at the holy place and its main court. Such a linkage between people and place leads to the unity of people and the creation of faith and special lifestyles such that these kinds of walkways can be introduced as a cultural pattern and global heritage. Currently, limited studies have been conducted to investigate the qualities of designing Pilgrimage walkways based on Iranian and Islamic culture. The methodology of this research is descriptive and analytical and data gathering has been done by library and field methods. The case study is Bagh Hassan Khan passage in the peripheral context of Imam Reza holy shrine in Mashhad city in Iran. In the process of research in the first step, the foundations and environmental qualities related to Pilgrimage walkways in the historical context around holy and Pilgrimage places have been investigated among conducted studies and the analysis of domestic and foreign documents and examples, and then the desired criteria and indicators have been extracted. In the second step, the quality assessment of the Bagh Hassan Khan passage has been conducted based on the opinions of residents and pilgrims and the hypotheses testing of the present research. To do so, 277 questionnaires have been distributed randomly in which related questions to the criteria of research have been provided. Excel and SPSS software have been used to analyze statistical data. The qualities of flexibility, liveliness and hygiene, readability and conceivability, safety and security, visual beauty and form, sense of belonging, warning and spiritual identification are the main criteria in the design qualities of Pilgrimage walkways in historical context around holy places which can provide a situation for pilgrims and tourists to enter a holy and spiritual place. The results of analyzing the opinions of pilgrims and users using the central concentration index show that more than half of the quality criteria are at the average and inappropriate level, also correlation analysis using the Chi-Square method shows that there is a significant relationship between the quality of Pilgrimage walkways and social interactions or problems. At the end of this research, some requirements and recommendations have been provided about the planning, designing, and composing rules for Pilgrimage walkways in the historical context around holy places.